Vandetanib plus gemcitabine versus placebo plus gemcitabine in locally advanced or metastatic pancreatic carcinoma (ViP): a prospective, randomised, double-blind, multicentre phase 2 trial. Issue 4 (April 2017) - Middleton, Gary; Palmer, Daniel H; Greenhalf, William; Ghaneh, Paula; Jackson, Richard; Cox, Trevor; Evans, Anthony; Shaw, Victoria E; Wadsley, Jonathan; Valle, Juan W; Propper, David; Wasan, Harpreet; et al.
Summary: Background: Erlotinib is an EGFR tyrosine kinase inhibitor that has shown a significant but only marginally improved median overall survival when combined with gemcitabine in patients with locally advanced and metastatic pancreatic cancer. Vandetanib is a novel tyrosine kinase inhibitor of VEGFR2, RET, and EGFR, all of which are in involved in the pathogenesis of pancreatic cancer. We investigated the clinical efficacy of vandetanib when used in combination with gemcitabine in patients with advanced pancreatic cancer. Methods: The Vandetanib in Pancreatic Cancer (ViP) trial was a phase 2 double-blind, multicentre, randomised placebo-controlled trial in previously untreated adult patients (aged ≥18 years) diagnosed with locally advanced or metastatic carcinoma of the pancreas confirmed by cytology or histology. Patients had to have an Eastern Cooperative Oncology Group (ECOG) score of 0–2 and a documented life expectancy of at least 3 months. Patients were randomly assigned 1:1 to receive vandetanib plus gemcitabine (vandetanib group) or placebo plus gemcitabine (placebo group) according to pre-generated sequences produced on the principle of randomly permuted blocks with variable block sizes of two and four. Patients were stratified at randomisation by disease stage and ECOG performance status. All patients received gemcitabine 1000 mg/m 2 as a 30-min intravenous infusion, weekly, for 7 weeks followed by a 1-week break, followed by a cycle of 3 weeks of treatment with a 1-week break, until disease progression, and either oral vandetanib 300 mg per day once daily or matching placebo. Patients and investigators were masked to treatment assignment. The primary outcome measure was overall survival (defined as the difference in time between randomisation and death from any cause or the censor date) in the intention-to-treat population. This trial has been completed and the final results are reported. The study is registered at EudraCT, number 2007-004299-38, and ISRCTN, number ISRCTN96397434. Findings: Patients were screened and enrolled between Oct 24, 2011, and Oct 7, 2013. Of 381 patients screened, 142 eligible patients were randomly assigned to treatment (72 to the vandetanib group and 70 to the placebo group). At database lock on July 15, 2015, at a median follow-up of 24·9 months (IQR 24·3 to not attainable), 131 patients had died: 70 (97%) of 72 in the vandetanib group and 61 (87%) of 70 in the placebo group. The median overall survival was 8·83 months (95% CI 7·11–11·58) in the vandetanib group and 8·95 months (6·55–11·74) in the placebo group (hazard ratio 1·21, 80·8% CI 0·95–1·53; log rank χ 2 1df 1·1, p=0·303). The most common grade 3–4 adverse events were neutropenia (35 [49%] of 72 patients in the vandetanib group vs 22 [31%] of 70 in the placebo group), thrombocytopenia (20 [28%] vs 16 [23%]), hypertension (nine [13%] vs 11 [16%]), leucopenia (12 [17%] vs 13 [19%]), and fatigue (17 [24%] vs 15 [21%]). No treatment-related deaths occurred during the study. Interpretation: The addition of vandetanib to gemcitabine monotherapy did not improve overall survival in advanced pancreatic cancer. Tyrosine kinase inhibitors might still have potential in the treatment of pancreatic cancer but further development requires the identification of biomarkers to specifically identify responsive cancer subtypes. Funding: Cancer Research UK and AstraZeneca.